An Epidemiological Study for Evaluation of Seasonal Variation in Road Traffic Accidents in the City of Ghaziabad (International Journal of Food and Nutritional Sciences, 2022)
Background: Injuries are increasingly recognized as a global public health epidemic. Everydayaround the world almost 16000 die from all types of injuries. According to WHO data, deaths from Road Traffic injuries account for 25% of all deaths from injury. Road traffic accidents represent epidemic of non-communicable disease in the present century. Objective: To evaluate the influences of seasonal variation in road traffic accident.Methodology: This study Prospective, descriptive and co-relational study was carried out at the Department of Forensic Medicine and Toxicology at Santosh Medical College and Hospital, Ghaziabad. All victims of road traffic accidents were the study subjects. The road accidents data were sourced from the archives of the Federal Road Safety Commission and Police Force while the climatic data were sourced from the Meteorological Agency.Result: The possible explanation for the fact that majority of accidents occurred during afternoon i.e. during 12-18 hours may be due to large number of vehicles on the overcrowded roads. In evening between 18-24 hours 32 (32.67%) accidents occurred, this may be due to work stress occurring during the day or intake of alcohol during these evening hours which make them careless, reckless with impaired judgment.Conclusion: It is possible to prevent traffic accidents or at least make them less harmful only with a life chain formed with the rings added into each other such as education, precaution, correction of technical requirements, consistent and conscious traffic control and wide organization of first aid services. Individuals, community and government should work in cooperation in order to transform that chain from a death chain into a safe transportation chain.